Empirical test of regional economic innovation and development along the Belt and Road - Kalonov, Mukhiddin; Shao Junling (GREEN ECONOMY AND DEVELOPMENT, 2023)
the article adopts the method of fully corrected least squares between groups, and uses the data from 2010 to 2018 (affected by the new crown epidemic after 2019, the data is not regular), to analyze the trade facilitation and import of intermediate goods in the regions along the “Belt and Road”. Conduct research with innovative development. The results show that the “Belt and Road” initiative has promoted trade facilitation,and enhanced innovation capabilities, but the phenomenon of regional imbalance is significant, which is greatly affected by the global economic situation.